Transcriptional regulation of the spo0F gene of Bacillus subtilis. - Lewandoski, M (1986)
We have cloned the early sporulation gene spo0F, which encodes an open reading frame of 124 codons. The putative Spo0F protein derived from this open reading frame, which has been shown to share homology with the Spo0A protein as well as several other regulatory proteins from Escherichia coli, Salmonella typhimurium, and Klebsiella pneumoniae, also shares homology with the E. coli EcoRI methyltransferase. We have shown by S1 nuclease mapping of in vivo transcripts that spo0F is regulated from dual promoters: RNA II was transcribed from an upstream promoter, and RNA I was initated 30 base pairs downstream from RNA II. The promoter sequences for RNA II, but not those for RNA I, conformed to the -10 region consensus sequence for sigma 43 promoters. RNA II was found in low amounts in exponentially growing cells but was not observed in stationary-phase cells, and the presence of RNA II was glucose insensitive. RNA I was found in low amounts in exponentially growing cells, increased three- to fivefold at the end of exponential growth, and remained at this higher level for at least 3 h into stationary phase. RNA I was repressed by glucose during exponential growth but not during stationary phase.